Posttraumatic stress symptoms in Croatian children exposed to war : a prospective study - Kuterovac-Jagodić, Gordana (Array, 2003)
This study examined symptoms of posttraumatic stress in 252 school-aged children from the city of Osijek in Croatia that was subjected to massive military attacks from Yugoslavian forces. The children's symptoms were assessed in 1994, while the war was still going on and 30 months later, when the war was over. In addition to changes in PTSD symptoms over time, the study examined the predictive power of the following variables: (1) different types and number of war traumata, (2) loss of social community (internal displacement), (3) the children's demographic characteristics (age and gender), (4) types of coping strategies and locus of control, and (5) the perceived availability of different kinds of social support. Although symptoms of posttraumatic stress declined over time, 10% of the children reported a severe level of symptomatology 30 months after the war. The results supported the hypothesized predictive power of all investigated factors for predicting short and long-term posttraumatic stress reactions.